Impactos ambientais da modernização agropecuária em Goiás - Villela, Pollyana de Macêdo (2016)
The process of modernisation in Goiás has intensified since the 1970 with the State’s strong intervention and the adoption of a highly technological package spread around the world. With the highly subsidized rural credits, economic incentives and investments in infrastructure and transport, the region began to gain notoriety due to agricultural development. Thus, in the course of agricultural modernization process, realized several environmental impacts related to loss of biodiversity, degradation and contamination of soil, water and air resources. Also socioeconomic impacts were observed, such as the rural exodus, the decrease of the job offer in the country, deepening social inequalities, the uncontrolled growth of cities, the development of the economy and of the municipalities, among others. In this context, the present study seeks to understand what are the environmental and socioeconomic impacts more significantly related to the expansion of the agricultural frontier in Goiás and at what level these impacts can be correlated. Therefore, at first, were selected twelve variables, as well as created two indexes that reflect the environmental impacts by using the factor analysis. The first index was called the Index of Livestock and Soil Degradation Impact. The second, in turn, was set to Index of Agriculture and Land Use Impact. The cities with the highest factorials scores for both indexes were: Nova Crixás, São Miguel do Araguaia, Caiapônia, Mineiros, Jataí and Rio Verde. From these data,it was possible to calculate the simple linear correlation analysis. So, the lack of correlation between the Index of Livestock and Soil Degradation Impact and Modernisation Index, i.e. not identified any linear correlation between these two indices. It appeared, therefore, that the environmental impact occurs regardless of whether the region is well upgraded or not. By correlating the same environmental impact index with the Index of Performance of Municipalities, which reflect the socio-economic dimension, it was noticed that there was a correlation, but with low intensity (r = 0.293). Thus, regions with good municipal performance impacted more the environment. Finally, by correlating the Modernization Index with the Index of Performance, also found a low correlation (r = 0.262). In this way, the counties that received more investments in technology, they developed their agricultural economy and stood out economically were those who showed greater socioeconomic